Group psychotherapy at a psychiatric day-hospital - Guimarães, Ana Celina Pires de Campos; Contel, José Onildo Betioli (Paidéia (Ribeirão Preto), 2009)
This study evaluated psychotherapy group at a psychiatric day-hospital, characterizing the groups' structure, content, frequency of verbalization and therapeutic management of meetings. Quantitative and qualitative methods with a categorical thematic approach were used. The patients were heterogeneous and groups were open with one-hour meetings. Six categories emerged from the thematic groups. The participants verbalized 56% of the 2,459 verbal accounts. During technical management of meetings predominated: support, emphasis on the here-and-now, and structure in guiding group behavior. The conclusion is that there were opportunities for patients to express themselves and these manifestations were therapeutically managed.